Design and Development of Portable Sports Post - Janon, Mohd Najib; Mohd Afiq Iskandar Mohd Affaidi; Mohd Adib Mohd Yani; Muhamad Haris Danial Mohamad Hikmal; Mohd Shahir Yahya; Hafsa Mohammad Noor (Multidisciplinary Applied Research and Innovation, 2024)
Sports are essential for a healthy life of university students. However, sports facilities such as playing courts for badminton, volleyball, and netball at the residential college are not enough for the number of active university students. Students have to walk for 15 to 20 minutes to get to the sports facilities area at the main campus. In this study, numerous Portable Sports Post ideas are compared using a variety of elements and criteria. This project aims to produce a convertible post for three types of sports: badminton, volleyball, and netball. This project also targets education centres with limited areas to provide portable sports equipment for their students to play the sport. This convertible design can save up more space in storage than other sports equipment. The development runs through concept design, configuration design and parametric design. The prototype is developed, tested, and analyzed based on performance, structure construction, and development cost.